DOP41 Achievement of corticosteroid-free clinical endpoints in subjects with ulcerative colitis: an analysis of the phase 3 ELEVATE UC 52 trial. (30th January 2023) - Sands, B E; Rubin, D T; Panés, J; Gecse, K B; Leung, Y; Goetsch, M; Wang, W; Shan, K; Woolcott, J; Smith, C C; Wosik, K; Schreiber, S W
Abstract: Background: Achievement of corticosteroid (CS)-free remission is an important long-term outcome in ulcerative colitis (UC). Etrasimod is an investigational, once-daily, oral, selective sphingosine 1-phosphate receptor 1, 4, 5 (S1P1, 4, 5 ) modulator in development for the treatment of moderately to severely active UC. This analysis of the ELEVATE UC 52 trial reports on the achievement of CS-free clinical endpoints. Methods: In ELEVATE UC 52 (NCT03945188), subjects (16-80 years) with moderately to severely active UC were randomised 2:1 to once-daily etrasimod 2 mg or placebo (PBO). ELEVATE UC 52 utilized a treat-through design comprising a 12-week induction period followed by a 40-week maintenance period. At study entry, subjects were permitted to receive concomitant treatment with CS (prednisone [≤20 mg/day], budesonide [≤9 mg/day], or equivalent]) provided they were on a stable dose 4 weeks prior to the screening endoscopy. Tapering of CS begun after the induction period. This analysis reports on achievement of CS-free (defined as no CS exposure in the 12 weeks immediately prior to week 52) clinical remission, CS-free endoscopic improvement, and CS-free symptomatic remission at week 52 in the ELEVATE UC 52 population, as well as CS-free clinical remission in pre-specified subgroups. Results: In ELEVATE UC 52 a significantly greater proportion of etrasimod-treated subjects had CS-free clinical remission (32.1% [88/274] vs 6.7% [9/135]; P <0.001), CS-free endoscopic improvement (36.9% [101/274] vs 10.4% [14/135]; P <0.001), and CS-free symptomatic remission (43.4% [119/274] vs 18.5% [25/135]; P <0.001) at week 52 vs PBO (Figure 1). Subgroup analyses of CS-free clinical remission demonstrated efficacy across subgroups including previous exposure to a biologic/JAKi, number of previous biologics/JAKis (0, 1, or >1), disease severity at baseline (MMS 4-6 or 7-9), and extent of disease (proctitis, left-sided colitis/proctosigmoiditis, or pancolitis) (Figure 2A-D). There was a trend towards greater benefit in subjects who were biologic/JAKi naive and subjects who had been exposed to 0 or 1 vs >1 prior biologic/JAKi. Conclusion: In ELEVATE UC 52, a greater proportion of etrasimod-treated subjects achieved CS-free clinical remission, CS-free endoscopic improvement, and CS-free symptomatic remission at week 52 vs PBO. These results were also consistent for multiple disease-specific subgroups, including those with and without prior exposure to biologics/JAKis. Notably, all ELEVATE UC 52 subjects who were in clinical and symptomatic remission at week 52 were also in CS-free clinical and CS-free symptomatic remission. 1 Reference: 1. Sandborn WJ, et al. Presented at: DDW 2022; May 24, 2022. Abstract 968a.